Penataan Kelembagaan Sekretariat Daerah Di Lingkungan Pemerintah Provinsi Banten - Asep Saripudin; Leo Agustino; Ipah Ema Jumiati (Jurnal Ilmu Administrasi Negara ASIAN (Asosiasi Ilmuwan Administrasi Negara), 2022)
In order to implement the provisions of Article 3 paragraph (1) of Peraturan pemerintah number 18 of 2016 concerning Regional Apparatuses, the Banten Provincial Government needs to stipulate Regional Regulations concerning the Formation and Composition of Regional Apparatuses. Based on this mandate, the Banten Provincial Government on November 23, 2016 promulgated the Banten Province Regional Peraturan Daerah Number 8 of 2016 concerning the Formation and Composition of Regional Apparatuses. The regional regulations are explained in the Peraturan Gubernur Number 83 of 2016 concerning the position, main tasks, functions, types, organizational structures and work procedures of the Banten Province Regional Apparatus. Regional apparatus organizations must be flexible and adaptive to regulatory changes and are expected to accommodate the needs of changes in society. For this reason, an organizational structure is needed to regulate the relationship between sections and subsections in the structure of an organization that is rich in functions. The regional apparatus organization is the regional secretariat which carries out the duties and functions of the regional secretariat. With this situation, the implementation of regional government, which is related to and or originates from the composition, organizational structure, as well as the implementation of the duties and functions of regional apparatus as the organizer of regional government affairs and identifies alternative arrangements of regional apparatus that are more in line with the needs of the vision and mission of the regional head. The data analysis technique in this study was carried out using qualitative methods through a juridical-normative approach, sociological empirical and institutional theory approach.